Eligibility and GDMT up-titration success in heart failure: A real-world assessment - Annika Weidenhammer; Suriya Prausmüller; Marc Stadler; Noel Panagiotides; Georg Spinka; Gregor Heitzinger; Henrike Arfsten; Guido Strunk; Anush Barkhudaryan; Clemens Partsch; Philipp Bartko; Georg Goliasch; et al. (PLoS ONE, 2025)
Background Implementation of GDMT in HFrEF remains incomplete. Prescription manners may vary based on the development of adverse effects. An HFA position paper proposed patient profiling and individualized prescription manners. This study aims to assess the eligibility for GDMT up-titration and its success in the context of clinical profiles in chronic severe HFrEF outpatients. Methods Clinical characteristics of 900 HFrEF patients at first presentation were assessed, and GDMT up-titration limiting factors were identified by applying thresholds of mutual consent. GDMT prescription was analyzed at 6 months and 1 year. Results 75% of patients had no GDMT up-titration limiting factor at baseline. Significant up-titration could be achieved in all four HF drug classes, especially within the first 6 months, irrespective of GDMT up-titration limiting factors (p ≤ 0.035 for administration and dosage, all drug classes). During up-titration, there was a balanced transition between up-titration limiting factors. 35% of patients received triple therapy on target dosages with a 2.6% one-year mortality rate. Regarding the HFA profiles, 62% of patients could not be classified into a specific HFA phenotype, including most severe patients. 98% of classifiable patients belonged to only four phenotypes, while GDMT up-titration could be achieved in all of these HFA profiles (p ≤ 0.007). Conclusion In this real-world study, 75% of patients with chronic severe HFrEF are eligible for GDMT up-titration towards target dosages. The clinical profile concept of the HFA might be adapted, as most classifiable patients can be up-titrated, and most severe patients are missed by the classification.